You want to solve 4 tan x - 1 = - 3*tan(-x)

Now tan -x = - tan x

4 tan x - 1 = - 3*tan(-x)

=> 4*tan x - 1 = 3* tan x

=> tan x = 1

=> x = arc tan 1

=> x = pi/4 + n*pi and 5*pi/4

For the equation x = pi/4 + n*pi and x = 5*pi/4 + n*pi

Posted on

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now